Character design for the Tapel Saga mobile game inspired by Malangan masks and Urban Legends - Arif, Novida Nur Miftakhul (Universitas Negeri Yogyakarta, 2024)
Character design is a crucial aspect of video games, requiring a solid understanding of design principles and an appreciation of the sources of inspiration, mainly when aiming to promote traditional culture, such as the Malangan masks.